Educational nursing technologies for self-care for people with intestinal elimination stoma: scientific evidence (Brazilian Journal of Health Research, 2024)
ABSTRACT| Introduction: Intestinal elimination ostomies can be understood as chronic conditions, which require the need for self-care. The promotion of this self-care can be carried out through educational technologies. Objective: To analyze scientific evidence on educational nursing technologies for self-care for people with intestinal elimination stoma. Methods: Integrative review, carried out in May 2024 via Portal Periódicos Capes with access to CAFe, in Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online, Scientific Electronic Library Online and EMBASE. After applying the eligibility criteria, ten articles were selected. Results: The main technologies found in the articles were digital media, such as platforms, software and applications, followed by printed booklets/guides, and videos. As a limitation of these technologies, the reach to illiterate people and those with hearing and/or visual impairments stands out. Conclusion: There is a predominance of strategies through educational technologies that involve technological resources, which aim to promote health, develop skills of people and health professionals, generate self-confidence and prevent complications, factors that favor the autonomy of people with a stoma.
Keywords: Stomy; Self-care; Intervention; Technology; Nursing